2022
DOI: 10.1002/ps.7164
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enhanced sensitivity of mutated β‐adrenergic‐like octopamine receptor to amitraz in honeybee Apis mellifera: An insight from MD simulations

Abstract: BACKGROUND: Amitraz is one of the critical acaricides/insecticides for effective control of pest infestation of Varroa destructor mite, a devastating parasite of Apis mellifera, because of its low toxicity to honeybees. Previous assays verified that a typical G protein-coupled receptor, ⊎-adrenergic-like octopamine receptor (Oct⊎2R), is the unique target of amitraz, but the honeybee Oct⊎2R resists to amitraz. However, the underlying molecular mechanism of the enhanced sensitivity or toxicity of amitraz to muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…For example, GPCRs, involved in numerous cellular signal transduction, are intrinsically allosteric proteins, activated by a diverse range of extracellular ligands and transmitting external environmental signals from one part of the protein to another (from extracellular to cytoplasmic). [53][54][55][56][57][58] Besides orthosteric sites recognized by endogenous agonists, many additional sites are spatially distinct but functionally linked to the orthosteric ones either positively or negatively, further increasing the complexity of GPCR function, and both ions and small molecules can act as GPCR allosteric modulators. 59,60 In addition, the binding of the allosteric effector might induce conformational or dynamics rearrangement of the PPI interface, and thereby interrupt or disrupt the recognition and interaction between PPI partners.…”
Section: Allosteric Regulation Of Upstream or Downstream Intermolecul...mentioning
confidence: 99%
“…For example, GPCRs, involved in numerous cellular signal transduction, are intrinsically allosteric proteins, activated by a diverse range of extracellular ligands and transmitting external environmental signals from one part of the protein to another (from extracellular to cytoplasmic). [53][54][55][56][57][58] Besides orthosteric sites recognized by endogenous agonists, many additional sites are spatially distinct but functionally linked to the orthosteric ones either positively or negatively, further increasing the complexity of GPCR function, and both ions and small molecules can act as GPCR allosteric modulators. 59,60 In addition, the binding of the allosteric effector might induce conformational or dynamics rearrangement of the PPI interface, and thereby interrupt or disrupt the recognition and interaction between PPI partners.…”
Section: Allosteric Regulation Of Upstream or Downstream Intermolecul...mentioning
confidence: 99%
“…Amitraz is a formamidine that targets tyramine and octopamine receptors in insects [ 104 106 ]. We chose to focus on the DEGs in the brain tissue of queens reared in wax contaminated with amitraz partly because our previous work showed that queens reared in amitraz-laden wax laid significantly fewer eggs than queens in any other treatment group [ 26 ] We therefore aimed to find DEGs in queens from the amitraz group that were involved in egg production and identified five genes of interest: GB40823 (Vitellogenin receptor), GB49544 (Vitellogenin), GB50425 (Maternal gene required for meiosis), GB47422 (Microtubule-associated serine/threonine-protein kinase 3), and GB45876 (Ribosomal protein S6 kinase beta-1-like) ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%